Tortious Acts Affecting Markets - Urs Schweizer (Sonderforschungsbereich/Transregio 15 - Governance and the Efficiency of Economic Systems (GESY), 2006)
The present paper examines an injurer causing a temporary blackout to a firm as the primary victim but also affecting customers and competitors of the firm. Reflecting existing legal practice, the paper investigates efficiency properties of the negligence rule granting recovery of private losses but to the primary victim only. The regime is shown to provide efficient incentives for precaution provided that the primary loss exceeds the social loss from accidents. The main contribution of the paper consists of an explicit analysis of markets affected by a temporary blackout of one firm. The analysis reveals that the private loss exceeds the social loss indeed if the market is less than fully competitive. Moreover, the net social loss remains positive, no matter which market structure prevails.
urn:nbn:de:bvb:19-epub-13445-1
Keywords: K13; K12; D62; 330